Stimulasi Kemampuan Berpikirk Logis Anak Speech Delay Melalui Model Pembelajaran Sentra Berbasis Wayang Pisang - Nur Aini; Ahmad Fachrurrazi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Children with speech delays often exhibit suboptimal logical thinking skills. Limitations in language skills and understanding instructions hinder children from recognizing patterns, solving basic problems, and understanding cause-and-effect relationships. Therefore, a planned, contextual, concrete, and enjoyable learning approach is needed to accommodate these children's unique characteristics. This study aims to analyze and describe the implementation of a learning center strategy using traditional banana puppet media to develop logical thinking skills in 3-year-old children with speech delays. A descriptive-qualitative approach was used. Data were collected through direct observation of children's activities, interviews with educators, and documentation of children's development. Data analysis was conducted qualitatively to evaluate the development of subjects' cognitive and logical abilities before and after the intervention. The results showed that the integration of learning center strategies (especially art centers and role-playing centers) with the use of concrete banana puppet media was able to attract attention, increase active participation, and stimulate children's thinking skills optimally. Through imaginative activities such as creating characters, role-playing, and storytelling using banana stem puppets, children naturally learn to construct logical thought processes and understand the concept of cause and effect. This concrete approach also supports the restoration of language aspects as a primary prerequisite for developing cognitive abilities in early childhood. The learning center strategy combined with the traditional banana puppet medium is effective in facilitating and stimulating the development of logical thinking skills in a natural, interactive, and non-pressurizing manner in 3-year-old children with speech delays.